PENGARUH PROFITABILITAS, DIVIDEN TUNAI, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sherlyn Evania; Etty Widyastuti (Prosiding Working Papers Series In Management, 2018)
Company value is a reflection of the stock market price of a company, which can guarantee the welfare or prosperity of shareholders. This research is conducted to analyze the effect of profitability, cash dividend, firm size on company value. Profitability is measured by using return on equity. Cash Dividend is measured using dividend payout ratio. Company size is measured using Ln Total Asset. Research data is secondary data in the form of annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2011-2015. The method of analysis used to test the hypothesis is the method of multiple linear regression statistics. The results showed that profitability negatively affect on company value. While the cash dividend and firm size have a positive effect on company value.  Keywords: profitability, cash dividend, firm size, company value.